Confronting bureaucracies and assessing value in the co-production of social design research. Issue 1 (2nd January 2019) - Kimbell, Lucy; Julier, Guy
ABSTRACT: This paper examines the issue of assessing the value of social design research. It locates the emergence of social design practice and research against a background in which public and social organisations are increasingly bureaucratised as a result of New Public Management and shifts to New Public Governance. Within universities, too, organisational processes and structures require research to demonstrate impact within an audit culture. Through the study presented in this paper, we claim that the bureaucracies found in contemporary academia are ill-equipped to adequately assess generative, impactful, and multi-sited research in which value is co-produced with diverse participants. This presents challenges when attempting to understand the value of social design research. Building on social research and studies of innovation policy, sustainable human-computer interaction and evaluation, we define social design research as inventive, contingent, and political. To address the issue of its evaluation, we propose two-stage social design research. In the first stage, research issues, questions, methods, data, and 'proto-publics' are assembled, which reveal the conflicting framings and ways that value is assessed. These are re-assembled in a second stage during which the research is stabilised. The findings have implications for research managers, academics and their partners, and university administrators.